Low bandgap copolymers based on monofluorinated isoindigo towards efficient polymer solar cells1. Issue 33 (7th September 2015) - Tomassetti, Mirco; Ouhib, Farid; Wislez, Arnaud; Duwez, Anne-Sophie; Penxten, Huguette; Dierckx, Wouter; Cardinaletti, Ilaria; Bovee, Ralf A. A.; van Pruissen, Gijs W. P.; Jérôme, Christine; Manca, Jean; Maes, Wouter; et al.
<x xml:space="preserve">Abstract</x> Low bandgap copolymers based on fluorinated isoindigo afford 5.0% efficiency in polymer solar cells.